Pengaruh Penyuluhan Hiv/Aids Terhadap Peningkatan Pengetahuan Tentang Hiv/Aids - Gusti Ayu Indraswari; Retno Heru Setorini; Wahyu Widi Astuti (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2015)
Background: Based on Statistics Indonesia in 2014 for HIV/AIDS cases showed an increase in the reportednumber of HIV/AIDS from January 1 to September 30, 2014 amounted to 22 869 people living with HIV and1.876 for people with AIDS. The cumulative number is highest at age 20-29 years and 9796 patients alreadyhave death. Yogyakarta Special Region has now ranks 14th as a province that has people living with HIV/AIDSin Indonesia’s largest. Total cumulative from 1 April 1987 to 30 September 2014 as many as 2,611 in phase HIVdan 916 has entered the phase of AIDSObjective: To determine the effect of education on HIV/AIDS to increase knowledge about HIV/AIDS in class XIstudent of SMAN 1 Kretek, Bantul, Yogyakarta.Methods: This research method is Pre-Experimental. The design of this study is one group pre-test post-test. Thesampling technique using proportional random sampling. Calculation of sample size was obtained by 46 respondents. The samples in this study was taken from each class with absent odd number, take 3 classes in a class of12 people and one taken 10 people.Results: The results of pre-test counseling about the effects of HIV/AIDS to increase knowledge of students ofclass XI SMA Negeri 1 Kretek, Bantul, Yogyakarta on HIV/AIDS, most students have less knowledge of 40 students(87%). Results of the post-test after counseling on HIV/AIDS to increase the knowledge class XI SMA Negeri 1Kretek, Bantul, Yogyakarta, most respondents have enough knowledge to 34 students (73.9%).Conclusion: The effect of counseling on HIV/AIDS is very effective for increasing knowledge about HIV/AIDS inclass XI student of SMAN 1 Kretek, Bantul, Yogyakarta. Evidenced by no significant difference before and aftercounseling on HIV/AIDS in class XI student of SMAN 1 Kretek, Bantul, Yogyakarta, ie 0.000 <0.05 significancevalue of 0.000 (p <0.05).Keywords: Education, Science, Youth